2004
DOI: 10.1074/jbc.m313955200
|View full text |Cite
|
Sign up to set email alerts
|

The Major Vault Protein Is a Novel Substrate for the Tyrosine Phosphatase SHP-2 and Scaffold Protein in Epidermal Growth Factor Signaling

Abstract: The catalytic activity of the Src homology 2 (SH2) domain-containing tyrosine phosphatase, SHP-2, is required for virtually all of its signaling effects. Elucidating the molecular mechanisms of SHP-2 signaling, therefore, rests upon the identification of its target substrates. In this report, we have used SHP-2 substratetrapping mutants to identify the major vault protein (MVP) as a putative SHP-2 substrate. MVP is the predominant component of vaults that are cytoplasmic ribonucleoprotein complexes of unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
174
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(176 citation statements)
references
References 58 publications
(50 reference statements)
1
174
1
Order By: Relevance
“…Phosphorylation of MVP is reported to depend on the presence of Mg 2+ (15), and EGF stimulation increases MVP tyrosil phosphorylation (12). Additionally, we have recently found that subcellular localization of PTEN is not regulated by PTEN phosphorylation (14).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Phosphorylation of MVP is reported to depend on the presence of Mg 2+ (15), and EGF stimulation increases MVP tyrosil phosphorylation (12). Additionally, we have recently found that subcellular localization of PTEN is not regulated by PTEN phosphorylation (14).…”
Section: Resultsmentioning
confidence: 92%
“…Erk has been shown to be imported to the nucleus by two coexisting mechanisms: passive diffusion and Ran-dependent active transport (22). Interestingly, MVP is reported to interact with phosphorylated p44/42 (Erks) in response to EGF stimulation (12). If MVP is involved in nuclear import of phospho-p44/42 as well, MVP-targeted siRNA should decrease nuclear phosphop44/42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The product of MVP that also genetically interacts with LAT has been postulated to act as a scaffold that modulates MAPK/ERK signaling. 57,58 Evidence is accumulating that it might be involved in the regulation of important cell signaling pathways, including PI3K/AKT, based on the finding that MVP binds several phosphatases and kinases such as PTEN, 59 PTPN11 (tyrosine phosphatase SHP-2), 58 as well as MAPK3 58 itself. The activity of the PI3K was shown to be essential to the signaling capacity of LAT-mediated complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, MVP expression is in many cases a significant and independent predictor of drug response [11]. While no direct function for MVP has been described, reports suggest nuclear translocation of target proteins such as PTEN [12], nuclear exclusion of chemotherapeutic drugs [13] and as a scaffold protein downstream of the EGFR [14]. The PTEN / MVP interaction has been previously observed in a yeast two hybrid system, and co-immunoprecipitations have been performed in human cancer cells [12].…”
Section: Discussionmentioning
confidence: 98%